Relationship between Floating Net Cage Farmers and Bosses in Haranggaol Horisan, Simalungun Regency, North Sumatra, Indonesia - Uly Artha Saragih; Erond L.Damanik (Journal of Citizenship, 2025)
Abstract: The study aims to understand the forms of social and economic relationships between floating net cage (FNC) farmers and bosses (tauke), as well as their impact on farmers’ welfare and the management of fair and sustainable FNC enterprises in Haranggaol Horisan Village, Simalungun Regency. The research employs a qualitative method with a descriptive approach through observation, in-depth interviews, and documentation. The informants consist of independent FNC farmers, FNC farmers partnered with bosses, members of fisheries associations, and the local village head. The results show two main types of relationships between farmers and bosses: bonded partnership relations and independent relations. Farmers who are bound to tauke experience a high level of dependency since all production needs are supplied by the tauke under a post-harvest payment system, while the selling price of fish is unilaterally determined by the tauke, weakening the farmers’ bargaining position. Conversely, independent farmers possess greater economic autonomy but face higher market risks. Such unequal relationships create a socio-economic structure that benefits the tauke while disadvantaging small-scale farmers. This study recommends strengthening farmers’ institutions through the establishment of cooperatives, government intervention in price regulation and access to capital, and ensuring transparency in partnership agreements to create more equitable relationships, improve farmers’ welfare, and maintain the economic sustainability of fisheries in the Haranggaol Horisan area. Keywords: relations, socio-economic, floating net cage, bosses